Analytical Profiling of Bioactive Phenolic Compounds in Argan (Argania spinosa) Leaves by Combined Microextraction by Packed Sorbent (MEPS) and LC‐DAD‐MS/MS. Issue 1 (9th September 2015) - Mercolini, Laura; Protti, Michele; Saracino, Maria Addolorata; Mandrone, Manuela; Antognoni, Fabiana; Poli, Ferruccio
Abstract: Introduction: The argan tree ( Argania spinosa ) is an endemic species from south‐western Morocco. Argan‐based preparations have been widely used in Moroccan traditional medicine for their biological properties, as well as for several cosmetic purposes. Whereas kernel, pulp of fruit and trunk have been extensively studied for their nutritional and pharmacological effects, relatively little is known about argan tree leaves. Objective: The main purpose of the present study is to investigate and characterise the bioactive phenolic fractions in both crude and aqueous extracts derived from argan tree leaves. Methodology: A qualitative profile of the antioxidant phenolic compounds in argan leaves was obtained by means of structural hypothesis based on UV spectra and mass spectrometric fragmentation patterns. Moreover, selected phenolics were quantified in argan leaves by using a fully validated method based on liquid chromatography coupled to diode array detection and tandem mass spectrometry (LC‐DAD‐MS/MS). All the extracts were purified by a fast and reliable microextraction by packed sorbent (MEPS) procedure, before analysing them by LC‐MS/MS. Results: Based on retention times, mass spectrometric fragmentation and UV spectra, 13 phenolic compounds were identified or tentatively elucidated from crude and aqueous extracts derived from Argania spinosa leaves, while seven compounds were quantified in both extracts. Conclusion: The obtained results could represent a first step towards a complete characterisation of the argan plant, its bioactive profiling and the valorisation of its by‐products as a source of potentially beneficial bioactive molecules. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : This is the first study addressed to the qualitative profile of antioxidant phenolic compounds in argan leaves, by means of a structural hypothesis based on UV, MS and MS/MS spectra. Moreover an original analytical method, based on LC‐DAD‐MS/MS, was developed and fully validated in order to quantify for the first time selected phenolics in both crude and aqueous leaf extracts, after purification by a novel microextraction by packed sorbent (MEPS).